ALLOMETRIC RELATIONSHIP IN THE CLAM KATELYSIA OPIMA (GMELIN) - Kalyanasundaram, M; Kasinathan, R (Indian Journal of Fisheries, 2011)
Analysis of covariance revealed length-weight relationship of Katelysiaopima to be significantly different in immature, male and female clams, and correlationcoeflScient to be significant at 0.025 level. The relationship between parameterslength (L), height (H), width (B), whole live weight (W), body wetweight (Wb), body dry weight